2010
DOI: 10.1182/blood-2009-04-217729
|View full text |Cite
|
Sign up to set email alerts
|

Generation of functional NKT cells in vitro from embryonic stem cells bearing rearranged invariant Vα14-Jα18 TCRα gene

Abstract: Establishment of a system with efficient generation of natural killer T (NKT) cells from embryonic stem (ES) cells would enable us to identify the cells with NKT- IntroductionNatural killer T (NKT) cells are characterized by their expression of an invariant receptor encoded by V␣14-J␣18 in mice 1 and by V␣24-J␣18 in humans. 2,3 Because the invariant receptor is used only by NKT cells and not by conventional T cells, NKT cells are a distinct lineage from conventional T cells. NKT cells produce both T helper 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 46 publications
(58 reference statements)
2
26
1
Order By: Relevance
“…In the 20-day culture system, iPSCs cultured on OP9/Dll-1 give rise to NKT cells bearing immature phenotypes similar to CD4 + CD8 + DP thymocytes in vitro as shown in Figure 2, while iPSC-derived NKT cells in the switch culture showed mature CD4 + or double-negative (DN) NKT cell phenotypes (Supplemental Figure 3B). These are similar to those obtained by the ESC culture as described (13). Therefore, Notch signaling inhibits phenotypic maturation of NKT cells.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…In the 20-day culture system, iPSCs cultured on OP9/Dll-1 give rise to NKT cells bearing immature phenotypes similar to CD4 + CD8 + DP thymocytes in vitro as shown in Figure 2, while iPSC-derived NKT cells in the switch culture showed mature CD4 + or double-negative (DN) NKT cell phenotypes (Supplemental Figure 3B). These are similar to those obtained by the ESC culture as described (13). Therefore, Notch signaling inhibits phenotypic maturation of NKT cells.…”
Section: Discussionsupporting
confidence: 70%
“…In fact, the iPSC-derived NKT cells obtained in the 25-day culture showed the ability to produce cytokines at levels similar to those of splenic NKT cells ( Figure 2D and Figure 4G). In particular, IFN-γ production was significantly high in the 25-day culture system using OP9/Dll-1 ( Figure 4G and Figure 2D), although, similar to ESC-derived NKT cells (13), iPSCderived NKT cells mainly produced IL-4 but not IFN-γ in the 20-day culture system using OP9/Dll-1 (Supplemental Figure 3C). Therefore, IFN-γ production by iPSC-derived NKT cells is apparently due to the duration of the culture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complete absence of NKT cells in mice deficient in recombinase subunits RAG-1 and RAG-2 or the TCR Jα18 segment demonstrated that successful rearrangement of TCRα gene segments Vα14 to Jα18 is absolutely necessary to the subsequent selection of DP thymocytes [25,26] . The signaling and transcription factors mentioned below act as master regulators on the NKT cell lineage, but distinct from conventional T cells [19] .…”
Section: Controls Of Nkt Cell Development and Homeostasismentioning
confidence: 99%